An interactive control architecture for interpersonal coordination in mirror game. (November 2018) - Zhai, Chao; Chen, Michael Z.Q.; Alderisio, Francesco; Yu. Uteshev, Alexei; di Bernardo, Mario
Abstract: In this work, an interactive control architecture based on velocity segments is developed to generate the human-like trajectories in the mirror game, a simple yet effective paradigm for studying interpersonal coordination, and the existence of velocity segments possessing a prescribed signature is theoretically guaranteed. Then an online control algorithm for the architecture is proposed to produce joint improvised motion with a human player or another virtual player while exhibiting some desired kinematic characteristics. Finally, the transition from solo motions to joint improvised motions is illuminated, and the proposed control architecture is validated by matching the experimental data. Highlights: Motor signature is constructed by integrating the desired kinematic feature into smooth point-to-point motions. The existence of constructed motor signature is guaranteed in theory. Solo motions with personalized motor signature are generated by consecutively assembling velocity segments. Joint improvised motions between two players emerge as a result of reconciling the imitation of respective motor signatures with their temporal correspondence of position and velocity.